Soccer Players of Winner of the Cup of Bosnia and Herzegovina and Kosovo Champion in Season 2016/17 and their Morphological Characteristics - Jovan Gardasevic; Dusko Bjelica; Ivan Vasiljevic; Marin Corluka; Fitim Arifi; Sami Sermaxhaj (University of Montenegro, Faculty for Sport and Physical Education, Montenegrin Sports Academy, 2020)
This research aimed to determine the differences among the top soccer players of a club in Bosnia and Herzegovina, FC Siroki Brijeg, and the top soccer players of a club in Kosovo, FC Trepca ´89, in the morphological characteristics and body composition. A sample of 37 subjects was divided into two sub-samples. The first sub-sample consisted of 22 players FC Siroki Brijeg, the average age of 24.00±6.22, the winner of the Cup of Bosnia and Herzegovina in the season 2016/17, while the other sub-sample consisted of 15 players of FC Trepca ´89 of the average age of 21.80±3.57, the champions of the Kosovo Championship in the season 2016/17. Soccer players were tested immediately after the end of the 2016/17 competition season. Morphological characteristics were evaluated using a battery of seven variables: body height, body weight, waist circumference, triceps skinfold, biceps skinfold, skinfold of the back, and abdominal skinfold. The body composition was evaluated using a battery of three variables: body mass index, fat percentage, and muscle mass. The significance of the differences between the players of the top two soccer clubs in the morphological characteristics and variables for assessing body composition was determined using a t-test for independent samples. The t-test results showed a statistically significant difference only in one variable triceps skinfold.